Maxent modeling for predicting the potential distribution of Arbutus andrachne L. belonging to climate change in Turkey - Sarıkaya, Ayşe Gül; Orucu, Omer K. (University of Kuwait, 2021)
Arbutus andrachne L., the strawberry tree, is an evergreen shrub or small tree in the Turkish flora and has broad uses. The wood is used for decorative purposes, packaging, and manufacturing furniture. The fruits are edible and used in treating many kinds of diseases. However, global warming might affect the abundance of this symbolic plant's distribution, especially at higher latitudes. This study was conducted to determine the expected effects of climate change on A. andrachne. For this purpose, Representative Concentration Pathway (RCP) 4.5 and RCP 8.5 were used to expect climate change scenarios for 2050 and 2070, and potential distribution areas of A. andrachne were presented. The results indicated that the distribution of A. andrachne would decrease in the southern regions of Turkey. However, the spread of the species could be expanded in the western and northern areas. It is also expected that there would be potential habitat losses, which would affect the distribution of A. andrachne.
Keywords: Arbutus Andrachne; Distribution; Maxent; RCP 4.5; RCP 8.5; Turkey